تطبيق نظام الحسبة في هيئة الشريعة الإسلامية في ولاية باوتشي بنيجيريا : دراسة تحليلية - غورم، موسى يعقوب (Kulliyah of Islamic Revealed Knowledge and Human Sciences,al-Jami'at al-Islamiyyah al- 'Alamiyyah Maliziya, 2020)
This research critically evaluates the application of Hisbah (Islamic community-oriented policing) under the Bauchi State Shari'ah Commission, Nigeria. Hisbah is a religious governorate; an official governmental body tasked with the responsibility of commanding good and forbidding evil. The duty of Hisbah is an individual obligation upon every capable Muslim man and woman just as it is a collective obligation that can be performed by a few on behalf of others. It turns to an individual obligation on all Muslims when no one performs it in the society. As we coexist with different faith communities in Africa, this motivates me to examine the implementation of Hisbah in Bauchi State where Muslims cohabit together with Christians and pagans. The establishment of Hisbah in Bauchi was necessitated by the need to stop the rising rate of immorality that had become pervasive in the state including drug abuse and alcoholism, adultery and fornication as well as corruption and fraud in commercial and financial dealings. Using a qualitative method, the research discusses the concept of Hisbah in the Shari'ah, followed by an explanation of the most obvious factors that led to its implementation in Bauchi State. It presents the historical development of Islam and the history of the establishment of the Shari'ah Commission which oversees the activities of Hisbah in the State. The research also analyses the contributions of the Hisbah Corps in the State. The study finds that the Shari'ah Commission in Bauchi State, Northern Nigeria, employs Shari'ah approaches in applying Hisbah within Bauchi societies, including resolving family and marital discord, financial settlement, inheritance issues. These help in reducing immoral acts and societal problems in the State. Therefore, this research strongly recommends that there is the need to establish more Shari'ah Commissions that carry out the tasks of bidding right and forbidding wrong in all Muslims countries as it is established in other countries like Kingdom of Saudi Arabia and some states in Northern Nigeria.